Photochemical Detoxification of Arsenic- and Mercury-Contaminated Soils: Geochemical Mechanisms and Pathways - Sunakbaeva Dilara; S. Ravichandran (International Journal of Photochemistry and Photochemical Research, 2026)
This study evaluates the geochemical aspects of soil detoxification in areas contaminated with arsenic (As) and mercury (Hg), emphasizing sustainable strategies for improving soil health and ensuring safe crop production. The research provides an ecological and toxicological assessment of regional soils and classifies them base on the concentration and mobility of toxic elements. Although the current levels of As and Hg do not yet present a critical risk to agricultural productivity, the steady increase in heavy metal accumulation due to industrial and agricultural activities necessitates effective remediation measures. To address this issue, a geochemical barrier composed of recycled poultry manure, marble chips (CaCO₃), and calcium peroxide (CaO₂) was designed and tested. The composite system functions as a multifunctional sorbent that stabilizes soil pH, enhances aeration, and reduces the bioavailability of heavy metals. Adsorption isotherm experiments demonstrated that mercury sorption capacity increased with higher CaO₂ content, while arsenic removal was strongly dependent on pH, reflecting distinct mechanisms of metal–sorbent interaction. The experimental results confirm that the proposed barrier effectively immobilizes toxic elements and transforms them into less mobile forms, contributing to soil detoxification and ecological restoration. The approach offers an environmentally friendly and economically viable solution for improving soil quality in contaminated regions. Overall, this study supports the integration of geochemical barrier technologies into sustainable land management and agricultural practices.
Keywords: Arsenic; Mercury; bioavailability; calcium peroxide; soil